2020
DOI: 10.3389/fphys.2020.530108
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Left Ventricular Global Strain in Anterior and Non-anterior Wall Myocardial Infarction With CMR Tissue Tracking

Abstract: Left ventricular (LV) myocardial dysfunction occurs after myocardial infarction (MI) is associated with the location, infarct size, and transmurality degrees of MI. The myocardial strain is a sensitive index used for the quantification of myocardium dysfunction. This study used Tissue-Tracking to evaluate whether the different location of MI would result in different myocardial dysfunction. One hundred patients diagnosed with MI who underwent cardiovascular magnetic resonance examination were included. The tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
4
5
0
Order By: Relevance
“…In our study, infarct extent and transmurality was not associated to GLS in the sub-acute phase, which means GLS is associated to IS, but not infarct extent or transmurality in this phase. Our study is in concordance with a CMR study by Li et al showing an association between infarct size and global strain [ 38 ]. While they found global radial, circumferential and longitudinal strain differed between patients with transmurality above or below 50% in the anterior wall myocardial infarctions, they did not find any difference in these global strain values in the non-anterior wall myocardial infarctions between the dichotomised transmurality groups.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, infarct extent and transmurality was not associated to GLS in the sub-acute phase, which means GLS is associated to IS, but not infarct extent or transmurality in this phase. Our study is in concordance with a CMR study by Li et al showing an association between infarct size and global strain [ 38 ]. While they found global radial, circumferential and longitudinal strain differed between patients with transmurality above or below 50% in the anterior wall myocardial infarctions, they did not find any difference in these global strain values in the non-anterior wall myocardial infarctions between the dichotomised transmurality groups.…”
Section: Discussionsupporting
confidence: 93%
“…The results indicated that segmental circumferential and longitudinal strains were decreased with increased levels of infarct transmurality. The change in circumferential strain in our study was similar to previous studies (22)(23)(24) which demonstrate that circumferential strain reflects the degree of transmurality. In addition, our results showed that regional radial strain was noticeably reduced with an increased degree of transmurality across three different circular parts of LV.…”
Section: Discussionsupporting
confidence: 91%
“…early (day 1-28 after MI) and late mortality of AWMI were greater in the anterior MI than inferior MI group [8]. The present study demonstrated that AWMI patients have larger IS and MVO and worse EF, which are consistent with existing literature [6,7,10], However, it remains controversial whether the location of MI is associated with poor prognosis after infarction, or whether the size of MI is more important than the anterior location of the infarction. In our opinion, larger IS always indicates greater myocardial necrosis and more serious myocardial dysfunction, and our univariate analysis showed that anterior MI location was not associated with MACE at medium-term clinic follow-up.…”
Section: Plos Onesupporting
confidence: 88%